Efficacy of delafloxacin versus moxifloxacin against atypical bacterial respiratory pathogens in adults with community-acquired bacterial pneumonia (CABP): Data from the Delafloxacin Phase 3 CABP Trial. (August 2020) - McCurdy, Sandra; Nenninger, Ashley; Sheets, Amanda; Keedy, Kara; Lawrence, Laura; Quintas, Megan; Cammarata, Sue
Highlights: When multiple diagnostic methods were performed, 30% of patients in a CABP clinical trial had a least 1 baseline atypical pathogen detected. 13.1% (68/520) of patients had a monomicrobial atypical infection and 2.3% (12/520) had polymicrobial all-atypical infections. For patients with Mycoplasma pneumoniae and Legionella pneumophila, serology yielded the highest number of diagnoses. For atypical pathogens, the rates of microbiological success were similar between the delafloxacin and moxifloxacin groups. A high proportion of favorable outcomes were observed across all delafloxacin baseline MIC values. Abstract: Objectives: To report atypical pathogens from clinical trial data comparing delafloxacin to moxifloxacin in the treatment of adults with community-acquired bacterial pneumonia (CABP). Methods: Multiple diagnostic methods were employed to diagnose atypical infections including culture, serology, and urinary antigen. Results: The microbiological intent-to-treat (MITT) population included 520 patients; 30% had an atypical bacterial pathogen identified (156/520). Overall, 13.1% (68/520) had a monomicrobial atypical infection and 2.3% (12/520) had polymicrobial all-atypical infections. Among patients with polymicrobial infections, Streptococcus pneumoniae was the most frequently occurring co-infecting organism and Chlamydia pneumoniae was the most frequently occurring co-infecting atypical organism. For Mycoplasma pneumoniae and Legionella pneumophila, serology yielded the highest number of diagnoses. Delafloxacin and moxifloxacin had similar in vitro activity against M. pneumoniae and delafloxacin had greater activity against L. pneumophila . Two macrolide-resistant M. pneumoniae isolates were recovered. No fluoroquinolone-resistant M. pneumoniae were isolated. The rates of microbiological success (documented or presumed eradication) at test-of-cure were similar between the delafloxacin and moxifloxacin groups. There was no evidence of a correlation between minimum inhibitory concentration (MIC) and outcome; a high proportion of favorable outcomes was observed across all delafloxacin baseline MICs. Conclusions: Delafloxacin may be considered a treatment option as monotherapy for CABP in adults, where broad-spectrum coverage including atypical activity is desirable.